E-commerce in China amid COVID-19 pandemic restrictions - Svetlana Yu. Revinova; Ekaterina A. Ivashchenko (RUDN Journal of Economics, 2021)
The COVID-19 pandemic has had a significant impact on all areas of life, including e-commerce. Most experts note a positive effect on e-commerce. E-commerce volume has grown all over the world. At the same time, structural changes took place; consumers changed their behavior and priorities. The purpose of the research is to study the role of e-commerce in China during the period of pandemic restrictions and analyze the statistical and structural changes in e-commerce during the epidemic. Quantitative and qualitative analysis is provided and the prospects for e-commerce in China are identified. When conducting the study, the methods of statistical and comparative analysis were used. The data sources were materials from the National Bureau of Statistics of China and other open sources. To determine the prospects for e-commerce, a model with an additive component was build. The data was deseasonalized, several trend variants were calculated, and the most suitable trend was selected, best approximating the sales data. The analysis showed that China has seen growth in e-commerce during the pandemic, but not as strong as expected. It is noted that before the pandemic, e-commerce grew at a reasonably rapid pace, and the pandemic only accelerated it a little. During the pandemic, those companies that had not previously used the Internet were forced to switch to new sales forms. The epidemic also prompted people to try many new products and services and then develop new consumer habits, which in the long term will continue the growth of e-commerce.